2013
DOI: 10.1016/j.seppur.2013.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of extraction solvents on the recovery of antioxidant phenolic compounds from brewer’s spent grains

Abstract: This study evaluated the efficacy of different solvents (methanol, ethanol, acetone, hexane, ethyl acetate, water, methanol:water mixtures, ethanol:water mixtures, and acetone:water mixtures) for extracting antioxidant phenolic compounds from brewer's spent grains (BSGs). The extracts were characterized regarding the contents of total phenols, flavonoids, proteins and reducing sugars. Antioxidant activity was determined by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical, and the ferric reducing antioxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
224
3
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 325 publications
(284 citation statements)
references
References 48 publications
33
224
3
5
Order By: Relevance
“…Recently, Meneses et al (2013) also evaluated the efficiency of different solvent compositions (methanol, ethanol, acetone, hexane, ethyl acetate, water, methanol:water mixtures, ethanol:water mixtures, and acetone:water mixtures) for extracting antioxidant phenolic compounds from BSG and reported that the extract produced with 60% v/v acetone had the highest content of total phenols (9.90 mg GAE/g). Again a higher phenolic content was found in the pilsen BSG used in this work when compared with the results of Meneses et al (2013). The higher values of phenolic content determined in the present work when compared with those from others works can be extensively discussed.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Meneses et al (2013) also evaluated the efficiency of different solvent compositions (methanol, ethanol, acetone, hexane, ethyl acetate, water, methanol:water mixtures, ethanol:water mixtures, and acetone:water mixtures) for extracting antioxidant phenolic compounds from BSG and reported that the extract produced with 60% v/v acetone had the highest content of total phenols (9.90 mg GAE/g). Again a higher phenolic content was found in the pilsen BSG used in this work when compared with the results of Meneses et al (2013). The higher values of phenolic content determined in the present work when compared with those from others works can be extensively discussed.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
“…Although, it is possible to conclude that the pilsen BSG sample studied in this work and the extraction procedure are responsible for the highest values of phenolic content determined in this type of samples. In fact, the extraction technique is probably the most influential factor since BSG is a lignocellulosic material which contains significant amount of phenolic acids esterified to the cell-wall, making their recovery harder (Meneses et al, 2013;Moreira et al, 2012). Generally, the conventional extraction techniques, such as mechanical agitation solvent extraction, Soxhlet extraction, enzymatic and alkaline hydrolysis extractions (Dvorakova et al, 2008;Mussatto et al, 2007;Szwajgier, Waśko, Targoński, Niedźwiadek, & Bancarzewska, 2010), applied for the recovery of these compounds are time and solvent consuming, submitting polyphenols to thermal degradation and decreasing the phenolic content of the extracts.…”
Section: Total Phenolic Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…The type of phenolics soluble in each of the extracting solutions tested is mainly different, because the phenolics include one or more of hydroxyl groups polar side attached directly to an aromatic ring non polar side . This stereochemistry differentiates phenolics according to their polarity variance, which affects the recovery of phenol from natural sources, when accomplished with solvent extraction, being the yield of the process depends strongly on the nature of the solvent 47 . In particular, methanol alcohol has been demonstrated to be more efficient in extraction of polyphenols with lower molecular weight while flavones with the higher molecular weight are better extracted with aqueous acetone 48 50 .…”
Section: Resultsmentioning
confidence: 99%
“…In particular, methanol alcohol has been demonstrated to be more efficient in extraction of polyphenols with lower molecular weight while flavones with the higher molecular weight are better extracted with aqueous acetone 48 50 . Acetone has also been found to be more efficient than other organic solvents for the extraction of phenolics from different raw materials such as brewer s spent grains 47 , Syzygium cumini 51 Acetone: water mixtures 50-95 v/v have been reported to be one of the most effective solvents for extraction of phenolics from different natural sources, especially from protein matrices, since this mixture is able to degrade polyphenol-protein complexes 52 . These differences could be attributed to the different methods of extraction and standards used, but also to different varieties, genomics and harvest season of the samples all these parameter affect the synthesis and accumulation of phenolics in some parts of the plant 41,53 .…”
Section: Resultsmentioning
confidence: 99%